Yield Progress in Forage Maize in NW Europe—Breeding Progress or Climate Change Effects? - Taube, Friedhelm; Vogeler, Iris; Kluß, Christof; Herrmann, Antje; Hasler, Mario; Rath, Jürgen; Loges, Ralf; Malisch, Carsten S. (Frontiers in Plant Science, 2020)
Yield increases in forage maize (Zea mays L.) in NW-Europe over time are well documented. The driving causes for these, however, remain unclear as there is little information available regarding the role of plant traits triggering this yield progress. Ten different hybrids from the same maturity group, which have typically been cultivated in Northwest Germany from 1970 to recent and which are thus representing breeding progress over four decades were selected for a two-year field study in northern Germany. Traits that were investigated included leaf area index, leaf architecture, photosynthesis, radiation use efficiency, root mass, root length density and turnover. Based on a mixed model analysis with these traits as co-variates, parameters related to leaf characteristics, in particular the number and length of leaves, the radiation use efficiency, and the leaf orientation were identified as most influential on the yield progress (0.13 tons ha-1 year-1). In contrast to our hypothesis, root biomass only increased negligibly in newer hybrids compared to older ones, confirming the ‘functional equilibrium’ theory for high input production systems. Due to an abundance of nutrients and water in such high input systems there is no incentive for breeders to select for carbon partitioning towards the rooting system. Breeding evidence to increase forage quality were also negligible, with no change in cob starch concentration, forage digestibility, nor NDF content and NDF digestibility. The observed increase in yield over the last four decades is due to a combination of increased temperature sums (~240 GDD within 40 years), and a higher radiation interception und radiation use efficiency. This higher radiation interception was driven by an increased leaf area index, with a higher number of leaves (16 instead of 14 leaves within 40 years), and longer leaves of newer compared to older hybrids. Future selection and adaptation of maize hybrids to changing environmental conditions are likely to be the key for high productivity and quality, as well as for the economic viability of maize growing and expansion in Northern Europe.